PENGARUH PEMBERIAN AROMATERAPI LAVENDER TERHADAP NYERI PERSALINAN KALA I FASE AKTIF PADA IBU PRIMIPARA : EVIDENCE-BASED CASE REPORT (EBCR) (Jurnal Kesehatan Siliwangi, 2022)
THE PAIN OF UTERINE CONTRACTIONS THAT CAN RESULT IN AN INCREASE IN THE SYMPATHETIC NERVOUS SYSTEM, CHANGES IN BLOOD PRESSURE, PULSE, BREATHING WITH SKIN COLOR AND IF NOT IMMEDIATELY OVERCOME WILL INCREASE WORRY, TENSION, FEAR AND STRESS. LABOR PAIN CAN BE TREATED USING COMPLEMENTARY THERAPY WITH AROMATHERAPY TECHNIQUES. LAVENDER AROMATHERAPY CAN AFFECT THE LIMBIC SYSTEM IN THE BRAIN THAT IS THE CENTRAL EMOTION, AND IS ABLE TO PRODUCE ENDORPHINS AND ENKEFALINE WHICH HAVE PAIN RELIEF PROPERTIES AND SEROTONIN THAT HAVE THE EFFECT OF RELIEVING ANXIETY AND TENSION. BECAUSE LAVENDER AROMATHERAPY HAS ANTICONVULSANT PROPERTIES, ANTIDEPRESSANTS, ANXIOLYTIC, AND AND CALMING AT THE TIME OF DELIVERY. EVIDENCE BASED CASE REPORT (EBCR) AIMS TO FIND OUT THE EFFECT OF LAVENDER AROMATHERAPY ON LABOR PAIN WHEN I ACTIVE PHASE IN THE VK ROOM OF HASAN SADIKIN HOSPITAL BANDUNG IS CARRIED OUT IN PUBMED, COCHRANE AND GARUDA PORTAL. OBTAINED 2 QUASI-EXPERIMENTAL ARTICLES BY WITAMA JULIANI, ET AL AND HILDA YANI, ET AL. WHICH IS IN ACCORDANCE WITH THE CRITERIA OF INCLUSION AND EXCLUSION AND HAS BEEN FILTERED BEFORE, THEN EXAMINED CRITICALLY. AFTER CRITICAL REVIEW OF BOTH ARTICLES IT IS STATED TO BE IMPORTANT AND CAN BE APPLIED TO THE PATIENT. THE ADMINISTRATION OF LAVENDER AROMATHERAPY TO LABOR PAIN WHEN I ACTIVE PHASE IN PRIMIPARA MOTHERS PERFORMED SHOWED EFFECTIVE MEASUREMENT OF PAIN INTENSITY USING NUMERIC RATTING SCALE (NRS) BEFORE BEING GIVEN LAVENDER AROMATHERAPY OBTAINED VALUE 5 (MODERATE PAIN) AND PAIN INTENSITY IN MATERNITY MOTHERS AFTER BEING GIVEN LAVENDER AROMATHERAPY OBTAINED VALUE 3 (MILD PAIN).